Do credit constraints affect households' economic vulnerability? Empirical evidence from rural China - Yan-ling Peng; Yanjun Ren; Hou-jian Li (Journal of Integrative Agriculture, 2021)
Poverty alleviation is still one of the major challenges in developing countries, especially in transitional economy like China. From the perspective of anti-poverty, this paper examines the impact of formal credit constraints (FCCs) and informal credit constraints (IFCCs) on economic vulnerability (EV) using the data from the China Household Income Project (CHIP) survey for 2013 (CHIPs 2013) of rural households. The potential endogeneity problem of credit constraints (CCs) is addressed by applying the control function approach within an ordered probit model. The results show that both FCCs and IFCCs have a robust positive and significant impact on the EV of rural households and that the impact of FCCs is greater than that of IFCCs. To identify the potential mechanisms through which CCs affect EV, the seemingly unrelated regressions are used and the potential intercorrelation among these mechanisms is examined. We find that the impact of CCs on EV is partly mediated by health, trust, per capita financial assets and per capita income, whereby health and per capita income contribute to most of the total indirect effect. Thus, policies focus on supply-side and demand-side to improve credit accessibility could reduce rural households' EV, especially through its positive effect on health and per capita income.
Keywords: 630; credit constraints; economic vulnerability; causal mediation mechanisms; rural China